PEMERATAAN KUALITAS HASIL BELAJAR - Mardiana Nurdin (Lembaga Pendidikan dan Tenaga Kependidikan (Center for Teacher Training) Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar in collaboration with Lecturer Consortium of Tarbiyah and Teacher Training, 2010)
This article deals two main points, the interpretation and mission of education, and the equality of educational quality as the main agenda of education in the contemporary discourse. This article is expository and argumentative in nature aiming at describing the real issue. Hence, an accurate investigation is needed to get conclusive findings.